Atrial Fibrillation: A Review of Recent Studies with a Focus on Those from the Duke Clinical Research Institute. (19th August 2014) - Rao, Meena P.; Pokorney, Sean D.; Granger, Christopher B.
Abstract : Atrial fibrillation is the most common arrhythmia and accounts for one-third of hospitalizations for rhythm disorders in the United States. The prevalence of atrial fibrillation averages 1% and increases with age. With the aging of the population, the number of patients with atrial fibrillation is expected to increase 150% by 2050, with more than 50% of atrial fibrillation patients being over the age of 80. This increasing burden of atrial fibrillation will lead to a higher incidence of stroke, as patients with atrial fibrillation have a five- to sevenfold greater risk of stroke than the general population. Strokes secondary to atrial fibrillation have a worse prognosis than in patients without atrial fibrillation. Vitamin K antagonists (e.g., warfarin), direct thrombin inhibitors (dabigatran), and factor Xa inhibitors (rivaroxaban and apixaban) are all oral anticoagulants that have been FDA approved for the prevention of stroke in atrial fibrillation. This review will summarize the experience of anticoagulants in patients with atrial fibrillation with a focus on the experience at the Duke Clinic Research Institute.